2023
DOI: 10.3389/fpsyg.2023.1155118
|View full text |Cite
|
Sign up to set email alerts
|

Work fatigue during COVID-19 lockdown teleworking: the role of psychosocial, environmental, and social working conditions

Abstract: BackgroundDuring national lockdowns in response to the COVID-19 pandemic, previously office-based workers who transitioned to home-based teleworking faced additional demands (e.g., childcare, inadequate homeworking spaces) likely resulting in poor work privacy fit. Previous office research suggests poor work privacy fit is associated with lower wellbeing and higher work fatigue. Emerging evidence suggests a relationship between childcare duties during pandemic teleworking and work fatigue. In addition to psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…In this work, we aim to fill the gaps identified by examining the impact of the work environment on the physical and psychological health of bank employees who were forced to work from home during the pandemic. Specifically, following Weber et al (2023), we differentiate three work environments: the physical environment, linked to home office conditions; the social environment, assessing the family interference with work; and the structural environment, addressing technological demands and, more specifically, the technological overload perceived by the worker as a consequence of the use of information and communication technologies for the performance of their work. We also examine the mediating role of family interference with work and technological overload and the moderating role of the support provided to teleworking by the organisation.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, we aim to fill the gaps identified by examining the impact of the work environment on the physical and psychological health of bank employees who were forced to work from home during the pandemic. Specifically, following Weber et al (2023), we differentiate three work environments: the physical environment, linked to home office conditions; the social environment, assessing the family interference with work; and the structural environment, addressing technological demands and, more specifically, the technological overload perceived by the worker as a consequence of the use of information and communication technologies for the performance of their work. We also examine the mediating role of family interference with work and technological overload and the moderating role of the support provided to teleworking by the organisation.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Following the Person-Environment fit theory developed by Edwards et al (1998), when individuals perceive a misfit between their needs and the characteristics of the environment, psychological, physical, and behavioral tensions arise, which in the long term can trigger physical and mental illnesses in the worker, such as stress, depression, poor sleep quality, or loss of concentration. In this sense, Weber et al (2023) identified three interrelated environments with potential effects on employee health: built environment, social environment, and structural environment.…”
Section: Theoretical Fr Ameworkmentioning
confidence: 99%
See 3 more Smart Citations